Famous works of art--and how they got that way - Nici, John B. (Rowman and Littlefield, 2015)
There are many reasons why works of art become famous; few have anything to do with quality. Art museums are filled with masterworks that are unknown to the general public. This book raises questions about how fame is achieved, and ultimately how a work either retains that fame, or passes from the public consciousness.